In-hospital management of type 2 diabetes mellitus. - Lien, L; Angelyn Bethel, M; Feinglos, M (2004)
The increasing prevalence of type 2 diabetes brings with it a need to understand the particular impact of hospitalization in this patient population. Type 2 diabetes has been shown to increase length of stay, infection, and mortality rates. To optimize inpatient care, it is important to understand target glycemic goals as well as in-hospital glucose monitoring and diabetes management goals. A practical review of regimens for subcutaneous insulin administration,intravenous insulin infusion, and inpatient use of oral agents is presented. Methods for achieving adequate preparation and education of the patient and family for discharge to the outpatient setting are also discussed.